Psychoeducation of SLB B Beringin Bhakti Teacher to Improve Emotional Well-being Through Spiritual Expressive Writing Therapy - Rina Kurnia; Mumtaz Afridah; Faika Maudina (Prophetic : Professional, Empathy, Islamic Counseling Journal, 2026)
Facing children with special needs requires unlimited patience and calmness, especially for teachers at SLB B Beringin Bhakti. Teachers with high emotional well-being are able to understand themselves, manage emotions, have self-confidence and have the strength to survive (resilience). Thus, an activity is needed to improve the emotional well-being of SLB teachers, one of which is through psychoeducation. Psychoeducation activities are carried out as an effort to provide alternative solutions to emotional well-being problems experienced. This psychoeducation activity aims to improve emotional well-being and provide emotional management skills for SLB B Beringin Bhakti teachers through Spiritual Expressive Writing Therapy. Furthermore, the method used is qualitative descriptive. The subject of this psychoeducation activity is SLB B Beringin Bhakti teacher which consists of 11 people. In its implementation, Spiritual Expressive Writing Therapy intervention is given through four stages, namely: rekognition/initial write stage, examination/writing exercise, juxtaposition/feedback, and application to the self. The results of this psychoeducational activity show that Spiritual Expressive Writing Therapy can improve the emotional well-being of SLB B Beringin Bhakti teachers. This is based on positive affect indicators, characterized by an increase in happiness, gratitude, meaning and optimism. There is also a decrease in negative affect indicators, including: decreased anxiety, level of frustration, lack of confidence, annoyance and anger at the situation.